Metabolic co-morbidities and psoriasis: The chicken or the egg? - Dalamaga, M; Papadavid, E (World J Dermatol, 2013)
Accumulating evidence supports that psoriasis may be a potential multisystem inflammatory disease associated with a range of co-morbidities showing an overlapping pathology and an important health impact such as metabolic diseases.   Psoriasis is associated with an increased risk of obesity, metabolic syndrome (Mets) and diabetes mellitus type 2 (t2DM), following a “dose-response” relationship from mild to severe psoriasis. Conversely, recent evidence from large prospective studies suggests that obesity constitutes a risk factor for psoriasis and psoriatic arthritis. Also, a dyslipidemic profile may precede psoriasis onset. Both obesity, Mets and psoriasis, characterized as chronic inflammatory states, stem from a shared underlying pathophysiology exhibiting common genetic predisposition and risk factors such as high caloric intake, physical inactivity and psychological stress. Excess weight may potentiate the inflammation of psoriasis through the deregulation of adipocytokines while, at the same time, it may help the development of Mets. Interestingly, recent translational data has shown that psoriasis, through increased T-helper inflammatory cytokines in skin and sera, may exert a plethora of effects on insulin regulation and lipid metabolism. Larger population-based prospective cohort and longitudinal studies are needed to unravel the association between psoriasis and metabolic co-morbidities. The recognition of the intricate complex interplay between psoriasis and metabolic co-morbidities may help dermatologists to be aware of associated metabolic co-morbidities in order to screen for metabolic diseases and manage holistically and effectively the psoriatic patient.